UJI COBA RANCANGAN MEDIA INTERAKTIF TERHADAP PENINGKATAN PENGETAHUAN TENTANG KARIES PADA ANAK SEKOLAH DASAR - Laut, Deru Marah; Alisa, Fitri Nur; Laela, Dewi Sodja; Putri, Megananda Hiranya (Poltekkes Kemenkes Bandung, 2023)
Dental caries are dental and oral diseases that often occur in communities. Knowledge deficit is an indicator of a high incidence of dental caries. Media is a tool for delivering messages from sender to recipient, which can be used in the process of providing information to increase knowledge. Interactive media is a form of media that contains interactivity or a mutually active relationship between humans (users) and products (media). This study aimed to determine the results of a feasibility test of interactive media design for caries and trials of interactive media design for caries on student knowledge. This was a quantitative study with a pre-experimental design using a one-group pretest-posttest design. Before the trials of interactive media design to students' knowledge, preceded by an assessment of the feasibility test of the interactive media design by media experts. Samples were taken by total sampling with a total sample of 54 fifth grade students at SDIT Daarul Jihad. The results showed that the feasibility test for interactive media design get a feasibility percentage of 93.8% with a very feasible category. The result also showed there was an increase in knowledge of dental caries with an average pre-test score of 66.48 to 90.37 in the post-test average score the average increasing score 26,39. The Wilcoxon test showed a significance level of 0.000 < 0.05. This showed that there was an influence from the results of the trials interactive media design for caries on the increasing knowledge of fifth grade elementary school students.